THE EFFECT OF WESTERN PHILOSOPHICAL REALISM (AL-MAŻHAB AL-WĀQI’Ī) TOWARD MODERN ARABIC LITERATURE / PENGARUH ALIRAN REALISME (AL-MAŻHAB AL-WĀQI’Ī) BARAT TERHADAP SASTRA ARAB MODERN - Mohammad Yusuf Setyawan (Lughawiyah: Journal of Arabic Education and Linguistics, 2021)
This study aims to find out the intricacies of philosophical realism (al-MaÅ¼hab al-WÄqiâ€™Ä«) and its influence on modern Arabic literature. It is undeniable that literary genre that grew up in the west have had a great influence on the development of literature in the world, including Arabic. This research was a literature review that used a qualitative descriptive method by examining and reviewing several related literature. The result showed that realism emerged as a response to the romanticism philosophy which tends to the subjectivity of writers and the depiction of objects that are full of imagination. Furthermore, the western realism has also influenced modern Arabic literature, both poetry and prose. Realism made Arabic poets aware that love poems were no longer relevant to the reality of the people who were in the midst of crisis due to colonialism. Writers began to invigorate the principles of statehood, nationality, and humanity. However, the adoption of western realism, in some aspects, is contrary to Islamic values. This philosophy directs literature towards materialism, atheism, fulfillment of physical needs, and so on.